Ultrasound‐Assisted Extraction of Fucoidan from Vietnamese Brown Seaweed Sargassum mcclurei and Testing Bioactivities of the Extract. Issue 14 (15th April 2020) - Thao My, Phan Le; Sung, Vo Van; Dat, Tran Do; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, fucoidan was extracted from the Vietnamese brown seaweed Sargassum mcclurei by ultrasound – assisted extraction method (UAE) using ethanol as a solvent. The effects of single factors on total polysaccharide (TPS) content were then investigated, followed by the screening of main factors affecting TPS content based on their effect sizes and p ‐values in analysis of variance. The response surface methodology using the Box‐Behnken design was applied to investigate simultaneous effects of four main factors including solvent‐to‐material ratio, extraction time, ultrasonic power, and extraction temperature. The optimal conditions for fucoidan extraction were identified with solvent‐to‐material ratio of 24 : 1 mL/g, extraction time of 49 min, ultrasonic power of 360 W, and extraction temperature of 54 ∘ C . The highest yield of TPS obtained under these conditions was 7.1203 mg/g. Besides, extraction of fucoidan using hot water method was also carried out to compare with UAE method in terms of TPS content. The bioactivity tests showed the extract had the anti‐oxidation activity with the half‐maximal inhibitory concentration (IC50 ) value of 0.4261 ± 0.0008 mg/mL, cytotoxic effect on breast carcinoma cells and human lung carcinoma with IC50 values of 95.80 ± 4.75 and 129.00 ± 0.66 μg/mL, respectively. Abstract : This research gives information about the ultrasound – assisted extraction procedure of fucoidan from Sargassum mcclurei using ethanol as a solvent. Single‐factor experiments were carried out in order to determine the influences of four factors including solvent‐to‐material ratio, extraction time, ultrasonic power, and extraction temperature on total polysaccharide content. The extract obtained under the optimal conditions were then tested biological activities showing potential beneficial effects on treatment of health problems.